Optimization of Four-Wheeled Patrol Units by Samapta Units in Order to Prevent Curat Crimes in the Jurisdiction of Sukoharjo Police Station - Axel Huwae (Akademi Kepolisian Republik Indonesia, 2023)
The author's final project raises the issue of